Achievements and Prospects of Global Broadband Seismographic Networks After 30 Years of Continuous Geophysical Observations. (7th September 2022) - Ringler, A. T.; Anthony, R. E.; Aster, R. C.; Ammon, C. J.; Arrowsmith, S.; Benz, H.; Ebeling, C.; Frassetto, A.; Kim, W.‐Y.; Koelemeijer, P.; Lau, H. C. P.; Lekić, V.; et al.
Abstract: Global seismographic networks (GSNs) emerged during the late nineteenth and early twentieth centuries, facilitated by seminal international developments in theory, technology, instrumentation, and data exchange. The mid‐ to late‐twentieth century saw the creation of the World‐Wide Standardized Seismographic Network (1961) and International Deployment of Accelerometers (1976), which advanced global geographic coverage as seismometer bandwidth increased greatly allowing for the recording of the Earth's principal seismic spectrum. The modern era of global observations and rapid data access began during the 1980s, and notably included the inception of the GEOSCOPE initiative (1982) and GSN (1988). Through continual improvements, GEOSCOPE and the GSN have realized near‐real time recording of ground motion with state‐of‐art data quality, dynamic range, and timing precision to encompass 180 seismic stations, many in very remote locations. Data from GSNs are increasingly integrated with other geophysical data (e.g., space geodesy, infrasound and Interferometric Synthetic Aperture Radar). Globally distributed seismic data are critical to resolving crust, mantle, and core structure; illuminating features of the plate tectonic and mantle convection system; rapid characterization of earthquakes; identification of potential tsunamis; global nuclear test verification; and provide sensitive proxies for environmental changes. As the global geosciences community continues to advance our understanding of Earth structure and processes controlling elastic wave propagation, GSN infrastructure offers a springboard to realize increasingly multi‐instrument geophysical observatories. Here, we review the historical, scientific, and monitoring heritage of GSNs, summarize key discoveries, and discuss future associated opportunities for Earth Science. Plain Language Summary: Global seismographic networks (GSNs) record information‐rich ground motion signals that allow scientists and nations to identify and quantify global earthquakes and other seismic sources, and to rapidly assess their significance and impacts on society. In addition to providing a global standard for the monitoring and assessment of such events, these networks provide unique high‐quality data that are fundamental to revealing Earth's structure and dynamic behavior. Scientific applications of GSNs, supplemented by regional data, include imaging the deep interior of the Earth and its plate tectonic system, modeling the structure and dynamics of the inner core, imaging and understanding the rupture of earthquake faults, detecting, discriminating, and characterizing nuclear and other explosions, and improving our general understanding of Earth's ubiquitous seismic wavefield and the unique information that it conveys from the deep interior to the surface and atmosphere of the planet. Leveraging the extensive and hardened infrastructure at these global observatories facilitates the recording of other signals of geophysical interest, such as the magnetic field, low frequency sound waves, and meteorological observations. We review the heritage of GSNs, including their history and resulting scientific achievements, and summarize future opportunities for these networks to contribute further to improved advancements in Earth science. Key Points: Long running globally distributed seismographic networks are fundamental to understanding Earth's interior structure and processes Networks have expanded beyond initial mid‐twentieth century design which were focused on recording signals from earthquakes and explosions Global seismic data combined with data from nearby geophysical instrumentation continue to facilitate new discoveries in Earth science